The Effect of Flow Rate of Adsorption Pretreatment in Removing Total Organic Carbon (TOC) Based on the SEM-EDX Test - Praditya S. Ardisty Sitogasa; Syahrul Munir; Euis Nurul Hidayah; Masterina Sufiati Farid (Future Science)
Adsorption is an accumulation of contact between gas or liquid molecules with a solid surface and some molecules attached to the surface. This study uses adsorption as a pretreatment of membrane processing. The adsorption process is affected by several factors, including the flow rate used in the adsorption process. This study aimed to determine the effect of water flow rate on the adsorption process in removing Total organic Carbon (TOC) using Calgon and Haycarb Adsorbent. The characteristics of the wastewater used are effluent of wastewater treatment from alcohol production that remains contains Total Organic Carbon (TOC). Variation of the flow rate used is 39 mL/minute, 29 mL/minute, and 23 mL/minute. The effect of flow rate on adsorption pretreatment in removing Total Organic Carbon (TOC) on Calgon adsorbent showed that 23 mL/minute was the most effective in reducing TOC values. On the other hand, using Haycarb absorbent on 23 mL/min flow rates was less effective in removing TOC values. The Haycarb adsorbent effectiveness is shown by the morphology of the initial and final results of EDX, where the adsorbent pore of Haycarb is not filled with absorbate.